Modern psychotherapies a comprehensive Christian approach - Jones, Stanton L.; Butman, Richard E., 1951- (Downers Grove, Ill. : IVP Academic, 2011)
This expanded and thoroughly updated second edition of the classic text continues to offer careful analysis and penetrating critiques of the myriad of psychotherapies now current in the field of psychology. With two new chapters on preventative intervention strategies and the person of the Christian psychotherapist, Modern Psychotherapies remains an indispensable tool for therapists and students.
The integration of psychology and Christianity / Stanton L. Jones and Richard E. Butman -- A Christian view of persons / Stanton L. Jones, Laura Miguélez and Richard E. Butman -- Classical psychoanalysis / Stanton L. Jones, Robert Watson and Richard E. Butman -- Contemporary psychodynamic psychotherapies / Michael W. Mangis, Stanton L. Jones and Richard E. Butman -- Behavior therapy / Stanton L. Jones, Kelly Flanagan and Richard E. Butman -- Cognitive therapy / Mark R. McMinn, Stanton L. Jones, Michael J. Vogel and Richard E. Butman -- Person-centered therapy / Terri Watson, Stanton L. Jones and Richard E. Butman -- Experiential therapies / Terri Watson, Tracey Lee, Stanton L. Jones and Richard E. Butman -- Family systems theory and therapy / David Van Dyke, Stanton L. Jones and Richard E. Butman -- Community psychology and preventative intervention strategies / Sally Schwer Canning -- Responsible eclecticism and the challenges of contemporary practice / Stanton L. Jones and Richard E. Butman -- Christian psychotherapy and the person of the Christian psychotherapist / Richard E. Butman and Stanton L. Jones.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Psychotherapy -- Religious aspects -- Christianity; Christianity -- Psychology; Pastoral psychology; RELIGION / Philosophy; Electronic books